MO348CLINICAL TRAJECTORIES AND IMPACT OF ACUTE KIDNEY DISEASE AFTER ACUTE KIDNEY INJURY IN INTENSIVE CARE UNIT: A 5-YEAR SINGLE-CENTER COHORT STUDY. (29th May 2021) - Orieux, Arthur; Prezelin-Reydit, Mathilde; Combe, Christian; Prevel, Renaud; Boyer, Alexandre; Rubin, Sébastien
Abstract: Background and Aims: Acute kidney injury (AKI) is observed in more than 50% of patients admitted in intensive care units (ICU) and more than 10% of them require renal replacement therapy (RRT) Acute kidney disease (AKD) has been recently proposed to describe a highly vulnerable period with pathophysiological process following AKI during which the patient could experience a decline in glomerular filtration and finally developed CKD. Patients suffering from AKI in ICU could have various renal trajectories and outcomes (early, late, or absence of recovery; early or late relapse; acute kidney disease (AKD); or chronic kidney disease (CKD)) after discharge. No cohort study described them accurately. Aims were to assess the various clinical trajectories after AKI in ICU and to determine risk factors for developing CKD taking into account the new concept of AKD and to assess the long-term incidence of CKD. Method: We conducted a prospective five-year follow-up study in a medical ICU in Bordeaux University Hospital (France). The patients who received invasive mechanical ventilation, catecholamine infusion or both and developed an AKI (defined by KDIGO criteria) from September 2013 to May 2015 were included. We excluded the patients with a previous estimated glomerular filtration rate (eGFR) of <90mL/min/1.73m2. AKD was defined as a condition wherein the criteria for AKI stage 1 or greater persists ≥7 days after exposure. CKD was defined by an eGFR of <60ml/min/1.73m2 at least 90 days after the AKI. Renal recovery was defined by serum creatinine ≤125% of serum basal creatinine. Using the Aalen-Johansen estimator to account for competing risks, we estimated the cumulative incidence of CKD. To estimate adjusted hazard ratios (HRs) we used standard Cox proportional hazard models adjusted for age, sex, hypertension, diabetes, cardiovascular history, SOFA and AKI stage. Proportional hazard assumptions were checked using Schoenfeld residuals. Violation of proportional hazard assumption for AKD was handled by using appropriate interaction terms with time, resulting in time-dependent HR. Results: 232 patients were enrolled. The age was 62 ± 16 years, 142/232 (61%) were male. AKI stage 1 was present in 62/232 (27%) patients, AKI stage 2 in 50/232 (21%), and AKI stage 3 in 120/232 (52%). Among patients with AKI, 65/232 (28%) recovered before day 7. At day 7, 106/232 (46%) had been progressing to AKD. AKD also developed secondary in 3/65 because of a second episode of AKI without recovery. Among the AKD patients, 21/109 (19%) recovered before day 90, 41/109 (38%) dead and 47/109 (43%) progressed to CKD (figure ). The cumulative incidence of CKD was 17 [12-21]% at 1-year follow-up and 30 [24-36] % at 5-years follow-up. This incidence was higher in AKD-patients (44 [35-54]%, and 48 [39-58]%) than in non-AKD patients (9 [1-16]% and 22 [10-34]%) after 1 and 5 years of follow-up, respectively (p=6.10 -5 ). The risk of developing CKD in AKD-patients was increased up to six months compared to those without AKD (HR 27.1 [7.9-93.5]; p<0.0001). Six months after AKI, the risk of progression to CKD was not statistically different between AKD patients and non-AKD patients (HR 2.45 [0.68 – 8.85]; p = 0.17). In this model only gender (male sex: HR 0.5 [0.3-0.9]; p= 0.02) was also significantly associated with CKD. Conclusion: There were many clinical trajectories after AKI in ICU. Risk for developing CKD remained during the 5 years of follow-up. AKD was the main risk factors for developing CKD only in the first 6 months. After, the risk was similar in AKD or non-AKD patients. Female gender was associated with CKD during all the follow-up. These patients need a specific follow-up after ICU discharge.